Physico-Chemical and Biochemical Properties of Oil Extracted from Pistacia lentiscus - MIZI*, ABDELKADER; DJEDAIA, SALAH (Asian Journal of Chemistry, 2009)
A physico-chemical study and biochemical properties of the oil extracted from Pistacia lentiscus is presented. This shrub of Mediterranean the maquis type is established in the area El Kala. The extracted oil was carried out by two modes of extraction, the parameters of the fat content are given. According to the results this oil is comparable with the olive-tree, it is composed by unsaturated fatty acids and a rather low content of vitamin E of the order 6.6 mg/100 g.